Estudio de factibilidad para la fabricación de alimento balanceado para pollos a base de semillas de girasol. - Cando Pullotásig, Hugo Cristóbal (2019)
The main objective of this research is to analyze the feasibility in the city of Latacunga, Cotopaxi province, for the production of balanced feed for chickens based on sunflower seeds. This research includes the analysis of the production of balanced feed for chickens taking advantage of the characteristics of the sunflower seed. The verification of the hypothesis was made through the Quantitative Research Methodology, because the feasibility of a project is based exclusively on the collection and analysis of numerical data.For data collection, information was sought in public institutions related to the avicola sector, records and studies dealing with the subject, so the main research technique to be used is the analysis of bibliographic and documentary contents.In the first place the total unsatisfied demand was determined, of which we are going to cover 8% of which on average for the five projected years is 1326 MT. Through this data the production capacity of the plant is determined and it was possible to determine the dimensions of the plans and the land that will be 1500m2. Within the economic and financial evaluation was determined a total of income and total of expenditures with which the value of the cash flow of the five years projected was stipulated, as well as the net present value (NPV), Internal Rate of Return (IRR), the period of recovery of the investment taking into account the value of money over time and lastly the cost benefit ratio was calculated, through this connection, it can be said that for every dollar invested, the project will generate $ 1.25 of income, concluding that this project is feasible